2009
DOI: 10.1093/ntr/ntn029
|View full text |Cite
|
Sign up to set email alerts
|

Smokers' responses toward cigarette pack warning labels in predicting quit intention, stage of change, and self-efficacy

Abstract: of succeeding. Malaysian smokers appear to respond to warnings in ways comparable with those from developed countries. IntroductionTobacco use is a global problem, resulting in a wide range of diseases and death and with great economic costs. By the year 2020, worldwide tobacco-related deaths are estimated to reach 10 million every year, two thirds of which will be in developing countries ( Mackay, Eriksen, & Shafey, 2006 Smokers' interest in quitting and their self-effi cacy for doing so mediate and predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 20 publications
4
52
0
Order By: Relevance
“…6 Health warnings constitute a powerful intervention for increasing knowledge about the specific harms of tobacco use 7 and for increasing thoughts and motivations to quit smoking among smokers in many countries including Thailand, Malaysia, Uruguay, Mauritius, Mexico, Australia and Canada. [8][9][10][11][12][13][14] Health warnings also have the potential to prevent smoking initiation among nonsmokers, including youth. 15 Smokers rate health warnings on cigarette packages as a prominent and credible source of information about the harms of tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…6 Health warnings constitute a powerful intervention for increasing knowledge about the specific harms of tobacco use 7 and for increasing thoughts and motivations to quit smoking among smokers in many countries including Thailand, Malaysia, Uruguay, Mauritius, Mexico, Australia and Canada. [8][9][10][11][12][13][14] Health warnings also have the potential to prevent smoking initiation among nonsmokers, including youth. 15 Smokers rate health warnings on cigarette packages as a prominent and credible source of information about the harms of tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…The self-efficacy item was measured on a five point scale, but for the purposes of this analysis it was dichotomised so that those with low self-efficacy (those who had responded that they were not at all or slightly sure they could quit within the next six months) were compared to those who had selected one of the remaining responses (moderately sure, very sure, extremely sure). This dichotomisation is consistent with a previous study (Fathelrahman et al, 2009), and its suitability was assessed by cross-tabulations of self-efficacy responses with other important variables. These showed that those who reported being not at all sure or a little sure that they could quit had similar responses on other questions.…”
Section: Who Endorses Brain-based Explanations Of Smoking?supporting
confidence: 63%
“…It was then expanded to several culturally distinct (e. g., France, Germany, The Netherlands) countries and countries that are both culturally distinct and developing (e.g., China, Thailand, Malaysia). This work is showing that while some policies appear to have essentially the same effects regardless of country (e.g., the impact of strong health warnings on packs [40,41]), some policies appear to have quite different impacts across countries. For example, there is high value placed on, and high compliance with laws mandating smoke-free public places in many jurisdictions, but they have been problematic in others, for example, Germany.…”
Section: Challenges Of Generalising From Research To Applications In mentioning
confidence: 85%